2016
DOI: 10.5535/arm.2016.40.6.1064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Balance, Proprioception and Skeletal Muscle Mass in Total Hip Replacement Patients With and Without Fracture: A Pilot Study

Abstract: ObjectiveTo determine whether there was a difference in balance, proprioception, and skeletal muscle mass among patients who undergo hip fracture surgery relative to and elective total hip replacement (THR).MethodsThirty-one THR patients were enrolled. The patients were categorized into two groups: fracture group (n=15) and non-fracture group (n=16). Berg Balance Scale (BBS) was used to balance the proprioception of the hip joint while a joint position sense (JPS) test was used to evaluate it. Skeletal muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…COP area and length in mechanography were corre-lated with K-FRAIL at 3 months after hip fracture surgery, whereas the COP variables were correlated with FAC and walking ability by Koval at 6 months. In terms of immobilization and deconditioning, similar to frailty, skeletal muscle mass index correlated with BBS at 3 months after total hip replacement surgery in a previous study [17]. Moreover, lower-limb muscle weakness remained at 6 and 24 months after hip surgery, although gait and balance function recovered [18,19].…”
Section: Discussionsupporting
confidence: 58%
“…COP area and length in mechanography were corre-lated with K-FRAIL at 3 months after hip fracture surgery, whereas the COP variables were correlated with FAC and walking ability by Koval at 6 months. In terms of immobilization and deconditioning, similar to frailty, skeletal muscle mass index correlated with BBS at 3 months after total hip replacement surgery in a previous study [17]. Moreover, lower-limb muscle weakness remained at 6 and 24 months after hip surgery, although gait and balance function recovered [18,19].…”
Section: Discussionsupporting
confidence: 58%
“…Low muscle attenuation (24) and low muscle mass (47, 54, 55) were associated with longer length of hospital stay and hospital readmissions (34, 44, 48, 56, 57). Other outcomes that were reported to be associated with low muscle mass included general morbidity (24, 34, 41), surgical complications (58), reduced physical function (57, 59), lower quality of life (59), higher inflammatory response after surgery (60), discharge destination to a nursing or rehabilitation facility (34, 56), and higher hospitalization costs (10, 61, 62). One study reported a null association between muscle mass and quality of life post-discharge (63); although the population was large (n=215), diagnoses within the sample were diverse (cancer and non-cancer patients), which could have concealed significant sub-group associations.…”
Section: Inpatient Settingsmentioning
confidence: 99%
“…Static balance/postural stability was assessed in 20 studies [ 11 , 35 , 37 53 , 63 ]; dynamic balance was assessed in 10 studies [ 34 , 36 , 41 , 52 , 54 59 ]; proprioception in terms of sense of joint position was assessed in 2 studies [ 60 , 61 ]; clinical scales and other test batteries for balance assessment were used in 10 studies [ 11 , 13 , 40 , 41 , 52 , 59 , 60 , 62 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Jo et al [ 60 ] investigating proprioception by means of hip joint position sense reported no differences between patients undergoing THA for osteoarthritis or after hip fracture 3 months after surgery, while Wang et al [ 61 ] reported that THA patients had higher mean absolute angle error than HR patients at 6 and 12 months from surgery; after 1 year and up to 36 months, both groups had similar absolute angle error. In either study, results were not compared with a control group of healthy age-matched participants.…”
Section: Resultsmentioning
confidence: 99%